The Relationship Between Strategic Management Implementation and Decision-Making Style in Enhancing Employee Satisfaction: Evidence from Islamic Cooperatives - Amar, Faozan; Jelita, Pepi Januar; Nugraha, Deni Pandu (Universitas Muhammadiyah Yogyakarta, 2025)
Research aims: This study aims to examine how strategic management implementation and decision-making styles contribute to employee satisfaction, with a specific focus on Islamic cooperatives. The study also explores the mediating role of organizational performance in this relationship.Design/Methodology/Approach: The research employs a quantitative approach using Structural Equation Modeling (SEM) with SmartPLS 4. Data were collected through questionnaires distributed to 124 employees of Islamic cooperatives, with 95 valid responses analyzed.Research Findings: The results indicate that strategic management does not directly affect employee satisfaction but exerts a significant indirect influence through organizational performance. Furthermore, among the various decision-making styles analyzed, only the dependent style showed a significant indirect effect on employee satisfaction through organizational performance.Theoretical Contribution/Originality: Grounded in dynamic capabilities theory, the study contributes to the literature by highlighting how strategic agility and inclusive decision-making, when aligned with Islamic values, enhance organizational outcomes and employee well-being. Moreover, the study introduces an integrated model linking strategic execution, decision behavior, and performance within the context of Islamic cooperatives.Practitioners/Policy Implications: The findings underline the importance for Islamic cooperative leaders to align strategic management practices with maqasid sharia principles and to adopt consultative decision styles that foster organizational trust, agility, and employee satisfaction.Research Limitations/Implications: The study is limited to a specific organizational context (Islamic cooperatives) and a relatively small sample size, which may affect generalizability. Future research could explore different cooperative models or apply a longitudinal approach.